Antibacterial activity of aqueous extracts of Indian chewing sticks on dental plaque: An in vitro study - Dola Srinivasa Rao; Tanuja Penmatsa; Alapati Kranthi Kumar; M Narendra Reddy; Nalam Sai Gautam; Nalam Radhika Gautam (Wolters Kluwer Medknow Publications, 2014)
The anti-microbial efficacy of aqueous extracts of Indian chewing sticks against different kinds of plaque bacteria in vitro was investigated. Supra-gingival plaque is cultured and subjected to the antibacterial activity of the aqueous extracts of chewing sticks (Neem, Acacia, Pongamia glabra, Achyranthes aspera, Streblus asper) separately. The results of the study demonstrate that all the five chewing sticks under study possess inhibitory potential against bacteria present in dental plaque mainly on aerobes. The antibacterial efficacy of aqueous extracts has antibacterial effects and could be used as a therapeutic agent and therefore, it appears to be potent anti-microbial agents that could be considered as a medicinal plant. Results of this study showed chewing sticks contained antibacterial agents, but the concentration and composition of the active substances differed among the plants.